Kajian Tax Avoidance: Peranan Ukuran Perusahaan dan Profitabilitas - Agintha, Nabilla Dwi (Maneggio: Jurnal Ilmiah Magister Manajemen, 2025)
The data used in this study are secondary data obtained through documentation studies, namely indirectly, namely investigating information based on the company's financial statements, organizational archives related to the study, such as organizational structure, number of employees, fields of work and organizational history. Furthermore, it is processed statistically with the SPSS 20.00 for windows program, namely the t-test model, F test and identification of the determinant coefficient (R2). The results obtained from this study indicate that partially company size has an effect on tax avoidance at PT. Mitra Sejahtera Deli Serdang and company profitability has an effect on tax avoidance at PT. Mitra Sejahtera Deli Serdang. Simultaneously, company size and profitability have a positive and significant effect on tax avoidance at PT. Mitra Sejahtera Deli Serdang. The Adjusted R Square value = 0.868, meaning that 86.8% of tax avoidance can be explained by the independent variables (company size and profitability) while the remaining 13.2% is explained by other variables not examined in this study.